The earliest evidence for crop cultivation during the Early Bronze Age in the southeastern Baltic. (April 2021) - Piličiauskas, Gytis; Vengalis, Rokas; Minkevičius, Karolis; Kisielienė, Dalia; Ežerinskis, Žilvinas; Šapolaitė, Justina; Skipitytė, Raminta; Robson, Harry K.
Highlights: Charred barley grains were dated to ca . 1300–1250 cal BC in western Lithuania. Fishing continued into the Bronze Age, supplemented by farming. The large FRE ( ca . 2000 years) was estimated for the Minija River. Abstract: The Early Bronze Age (1800–1100 cal BC) is among one of the most poorly understood prehistoric periods in the southeastern Baltic region. Here, we present the multidisciplinary results obtained from the recent excavations undertaken at the site of Kvietiniai in western Lithuania, including radiocarbon ( 14 C) measurements and the stable isotope analysis of charred barley ( Hordeum vulgare ) grains. Our results provide the earliest direct evidence for crop cultivation in the southeastern Baltic region ( ca . 1300–1250 cal BC), and link it to an as yet poorly known cord-impressed coarse pottery tradition. Moreover, the Freshwater Reservoir Effect (FRE) of the nearby Minija River was calculated, ca . 2000 years today with a terminus ad quem of 780 ± 57 years during prehistory. Consequently, our findings have implications for understanding the cultural and economic development of the Bronze Age in the region, and demonstrate that crop cultivation was adopted ca . 1500 years after the initial integration of animal husbandry in the Early Neolithic.